Print and pleasure : popular literature and entertaining fictions in colonial North India - Orsini, Francesca (Ranikhet : Permanent Black, 2009)
History of commercial publishing in nineteenth century North India.
Includes bibliographical references (p. [285]-298) and index.
Keywords: Publishers and publishing -- India, North -- History -- 19th century; Books and reading -- India, North -- History -- 19th century; Popular literature -- India, North -- History and criticism; Hindi fiction -- 19th century -- History and criticism; Urdu fiction -- 19th century -- History and criticism